If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 8 = (6 + -1x) Reorder the terms: 8 + 3x = (6 + -1x) Remove parenthesis around (6 + -1x) 8 + 3x = 6 + -1x Solving 8 + 3x = 6 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 8 + 3x + x = 6 + -1x + x Combine like terms: 3x + x = 4x 8 + 4x = 6 + -1x + x Combine like terms: -1x + x = 0 8 + 4x = 6 + 0 8 + 4x = 6 Add '-8' to each side of the equation. 8 + -8 + 4x = 6 + -8 Combine like terms: 8 + -8 = 0 0 + 4x = 6 + -8 4x = 6 + -8 Combine like terms: 6 + -8 = -2 4x = -2 Divide each side by '4'. x = -0.5 Simplifying x = -0.5
| 2(x-16)-5(x-3)=18 | | 6[x-10]+8=26 | | 7z+17=6z+8 | | 16x+5=-37 | | (x+9)(x-3)=(x+1)(x+1) | | [n/10]=3 | | 8-(3+b)=b+-9 | | -[p-4]+9=8 | | -3r-6r=-9 | | 3(x-4)-4(3-x)=x+3-(x-5) | | 5(x^2-x-12)=0 | | N/-0.5=13 | | 42=-6+4b | | 4y^2-81y=0 | | -7u+3(u+7)=29 | | (f-1)=45 | | -(xy+y^2-4)= | | 18-6x=2x+34 | | 40+12.50= | | 5(x^2-x-30)=0 | | 39=-10x-1 | | 9x+7=20x-7 | | 12.50+40= | | -2+v=4 | | 1.98=(8.99*10^9)*(11.7*10^-6)*(29.9*10^-6)/r^2 | | -2z-7y=7+7 | | 4x-12x+3=5 | | x-2(-2x+5)=2 | | 12x+22=-9x-41 | | -144=-8x | | 3n-8=32n | | x=ky+f |